ANALISIS DAMPAK KOMPENSASI, KEPUASAN KERJA DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PERUSAHAN PADA MASA PANDEMI - Ilyas, Fadli (Journal of Industrial Engineering & Management Research, 2022)
This research was conducted to find out how big the impact of compensation, job satisfaction and leadership on the performance of company employees in the midst of an effort to survive the prolonged covid pandemic conditions. The method used is a quantitative research method. The sampling technique was done by random sampling. Data was obtained by distributing questionnaires to 35 respondents from 100 employees. The analytical method used is multiple linear regression and t test. The results of the hypothesis test (t test) show that the variables of job satisfaction (X2) and Leadership (X3) have no effect on performance. Because based on the results of the analysis that affects performance only compensation (X1), then to improve employee performance, what needs to be done is to improve compensation indicators.